1993
DOI: 10.1002/ajim.4700240108
|View full text |Cite
|
Sign up to set email alerts
|

A health survey of workers in the pentachlorophenol section of a chemical manufacturing plant

Abstract: During 1968 to 1985, 109 workers who had been engaged in the production of pentachlorophenol, using non-gamma isomers of hexachloroclohexane (BHC) as the raw material, were surveyed. Endemic chloracne among them had been noted since 1974. The prevalence of chloracne was 73.4% (80/109) in total and 95.2% (20/21) in a trichlorobenzene (TCB) tank area where dioxin and dibenzofurans levels were thousands of ppm. To our knowledge, PCDDs and PCDFs have not previously been reported from thermal decomposition of BHC. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…Many studies have reported that PCP production may be a very important source of polychlorinated dibenzo-p-dioxin and dibenzofurans (PCDD/Fs) (Hagenmaier and Hermann, 1987;Rappe et al, 1991;Bao et al, 1995;Zheng et al, 1997;Xu et al, 2000). Endemic chloracne among the workers in a plant located in this chemical industry zone had been noted since 1974 (Cheng et al, 1993). The prevalence of chloracne was 73.4% in total and 95.2% in trichlorobenzene tank area workers where PCDD/Fs levels were up to thousands of ppm.…”
Section: Introductionmentioning
confidence: 98%
“…Many studies have reported that PCP production may be a very important source of polychlorinated dibenzo-p-dioxin and dibenzofurans (PCDD/Fs) (Hagenmaier and Hermann, 1987;Rappe et al, 1991;Bao et al, 1995;Zheng et al, 1997;Xu et al, 2000). Endemic chloracne among the workers in a plant located in this chemical industry zone had been noted since 1974 (Cheng et al, 1993). The prevalence of chloracne was 73.4% in total and 95.2% in trichlorobenzene tank area workers where PCDD/Fs levels were up to thousands of ppm.…”
Section: Introductionmentioning
confidence: 98%
“…The prevalence of chloracne was 73.4% (80/109) in total and 95.2% (20/21) in a trichlorobenzene (TCB) tank area where dioxin and dibenzofurans levels were thousands of ppm. 11 Another survey in 3,538 workers of a factory exposure to TCDD, 11% were found to have chloracne. 12 In addition, a widely publicized example was the accident occurred at a chemical plant near Seveso of Italy in 1976.…”
Section: Etiology Of Chloracnementioning
confidence: 99%
“…It has been shown that dioxins are impurities that are formed during the production process of PCP (Cheng et al, 1993). The 12 chloracne cases were similar in severity of their visible clinical manifestations.…”
Section: Study Subjectsmentioning
confidence: 69%